Management of Intraoperative Complications in Arthroscopic Primary Anterior Cruciate Ligament Reconstruction - Charalambous, Charalambos P.; Alvi, Farhan; Sutton, Paul M. (The Journal of Knee Surgery, 2015)
Arthroscopic anterior cruciate ligament reconstruction is a commonly performed procedure which is technically demanding and involves multiple surgical steps with the potential for a wide range of intraoperative complications. In this article, we review these potential complications and give algorithms for dealing with them based on our experience and published evidence. We discuss the use of both bone-patellar tendon-bone and hamstring grafts and examine complications associated with suspensory button and interference screw fixation.
Keywords: knee; reconstruction; ACL; complications